The Role of the Parang Ilang in Iban Material Culture in Sarawak - Asri, Adilawati; Tugang, Noria; Ajop, Abigail Jelembai Christopher; Mukresh, Muyyar (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
This study explores the parang Ilang through the lens of Iban civilisation and culture, highlighting its significance as a symbol of their historical grandeur and civilisational achievement in Sarawak. The parang Ilang is a traditional tool of logistics that plays a crucial role in Iban material culture in Sarawak. Beyond being a tool for defence and hunting, the Iban parang Ilang symbolises social status, heroism, strength, courage, and heritage passed down through generations. It also serves as a cultural identity marker, reflecting intellectual values and aspirations that are deeply rooted in everyday life. However, various factors have altered the cultural patterns of the Iban during the colonial era. Additionally, modernisation and globalisation have weakened contemporary Iban society’s ability to comprehend the origins and significance of the parang ilang within their material culture. In light of this, the present study aims to analyse the role of the parang Ilang within the Iban material culture, encompassing its use in warfare, traditional rituals, traditional healing practices, and as a legacy and heirloom. The research employs a qualitative ethnographic methodology grounded in fieldwork, utilising participant and non-participant observations as well as triangulated interviews with informants.  Fleming’s theory (1974) is applied to data analysis. The findings reveal that the parang Ilang retains relevance and continues to be practised within contemporary Iban material culture. Ultimately, this study highlights the importance of appreciating the role of parang Ilang, thereby enabling younger generations to better recognise and understand the struggles and cultural heritage of their ancestors before the advent of modernity. Full text: PDF